Model‐based loss minimisation scheme for wind solar hybrid generation system using (grid‐connected) doubly fed induction generator. Issue 6 (1st July 2016) - Parida, Adikanda; Chatterjee, Debashis
Abstract : A wind–solar hybrid system using doubly fed induction generator (DFIG) is described in this study. An optimum rotor current control strategy considering minimum losses of the induction generator over entire period of operation is proposed. In the proposed scheme, a solar photovoltaic (PV) unit of appropriate capacity has been augmented with the rotor circuit of the DFIG along with a marginal battery backup to supplement the rotor power in order to maintain continuity of power generation. The active power fluctuations at the stator terminals of the DFIG can be minimised as both solar PV and wind energy can complement each other during lean periods of either of the sources. The proposed scheme has been simulated and experimentally validated with a 2.5 kW DFIG using dSPACE CP1104 module, which produced satisfactory results.